2022
DOI: 10.22214/ijraset.2022.39911
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Effect by Heavy Metals as Pollutants on Fertile Soil

Abstract: There are rising geologic and anthropogenic processes and as a result, now a days soils polluted by heavy metals have become more common and it is a problem across the globe. Soil polluted due to heavy metal can be freed from pollutants effectively by use of bioremediation process. It's a very well-known process and is used in situ, making it ideal to make soil free from pollutants as a part of crop establishment as well as restoration of soil which are being treated. Microorganisms as well as plants uses a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hexavalent chromium (Cr(Ⅵ)) is a well‐known pollutant that originates from effluents of several industrial processes such as tanning, electroplating, dyeing, and wood preservation (WHO, 2013). In industrial wastewaters, high chromium concentrations were found in tannery effluents (0.7–345 mg/L) (Dhungana & Yadav, 2009), textile mill effluents (0.11–0.21 mg/L) (Bhardwaj et al, 2014), and chrome plating industry wastewater (5722 mg/L) (Karegar et al, 2015). For natural waters, lower chromium concentrations have been described; for example, 0.1–117 μg/L in freshwater and 0.2–50 μg/L in seawater (Shanker & Venkateswarlu, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Hexavalent chromium (Cr(Ⅵ)) is a well‐known pollutant that originates from effluents of several industrial processes such as tanning, electroplating, dyeing, and wood preservation (WHO, 2013). In industrial wastewaters, high chromium concentrations were found in tannery effluents (0.7–345 mg/L) (Dhungana & Yadav, 2009), textile mill effluents (0.11–0.21 mg/L) (Bhardwaj et al, 2014), and chrome plating industry wastewater (5722 mg/L) (Karegar et al, 2015). For natural waters, lower chromium concentrations have been described; for example, 0.1–117 μg/L in freshwater and 0.2–50 μg/L in seawater (Shanker & Venkateswarlu, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Textile manufacturing factories consistently discharge waste containing excess dangerous metals such as copper, lead, nickel, cadmium and chromium into their surroundings ( Bhardwaj et al . 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Textile manufacturing factories consistently discharge waste containing excess dangerous metals such as copper, lead, nickel, cadmium and chromium into their surroundings (Bhardwaj et al 2014). Thus, copper and dye are highly likely to be simultaneously found among industrial waste in the environment.…”
Section: Introductionmentioning
confidence: 99%